2022
DOI: 10.1371/journal.pone.0263213
|View full text |Cite
|
Sign up to set email alerts
|

Association between skeletal muscle mass or percent body fat and metabolic syndrome development in Japanese women: A 7-year prospective study

Abstract: Previous cross-sectional studies have indicated that low relative appendicular lean mass (ALM) against body weight (divided by body weight, ALM/Wt, or divided by body mass index, ALM/BMI) was negatively associated with metabolic syndrome (MetS). Conversely, previous cross-sectional studies have indicated that the absolute ALM or ALM divided by squared height (ALM/Ht2) were positively associated with MetS. The aim of this longitudinal study was to investigate the association between low absolute or relative ske… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…The positive association between skeletal muscle mass and insulin resistance in overweight and obese individuals is consistent with prior studies, which have shown that sarcopenia contributes more to insulin resistance in older adults than sarcopenic obesity or obesity alone [ 3 , 4 , 12 , 17 ]. It is known that higher lean mass is often accompanied by higher fat mass in older adults [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The positive association between skeletal muscle mass and insulin resistance in overweight and obese individuals is consistent with prior studies, which have shown that sarcopenia contributes more to insulin resistance in older adults than sarcopenic obesity or obesity alone [ 3 , 4 , 12 , 17 ]. It is known that higher lean mass is often accompanied by higher fat mass in older adults [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…ALM was significantly associated with insulin resistance in overweight and obese individuals. This is similar to a longitudinal, prospective cohort study where an association between appendicular lean mass and metabolic syndrome was found [ 4 ]. A cross-sectional study also found that decreased lower limb muscle mass and appendicular muscle mass was associated with increased insulin resistance [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies indicate that several diseases related to metabolic syndrome (MetS) are associated with low MQI/BMI and increased mortality due to insulin resistance, which has an inverse correlation with insulin sensitivity [34]. Our study found that individuals with obesity exhibited a worse MQI, which might be linked to insulin resistance and high values in the MetS parameters [35,36], with statistically significant correlation coefficients in both cases, a condition observed in our current report on obese women with and without cancer [34].…”
Section: Discussionmentioning
confidence: 46%
“…Five trials were performed at 15‐s intervals, and the average of the two highest outputs (W) was employed. LEP divided by body weight was used for the analysis 23 …”
Section: Methodsmentioning
confidence: 99%